1999
DOI: 10.1007/s004010051106
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Western immunoblotting procedure for bovine PrP Sc detection and its use as a rapid surveillance method for the diagnosis of bovine spongiform encephalopathy (BSE)

Abstract: In this report we document the results of several independent studies testing the sensitivity, specificity and reliability of the Prionics Western blotting (PWB) procedure to detect bovine and ovine disease-specific, protease-resistant prion protein (PrP(Sc)). Validation of the technique was obtained by blind analysis of samples from cattle affected with bovine spongiform encephalopathy (BSE), clinically normal animals or cattle with neurological diseases unrelated to BSE. Overall, very high sensitivity, speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
111
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(115 citation statements)
references
References 14 publications
1
111
0
2
Order By: Relevance
“…Transmissible spongiform encephalopathies (TSE) or "prion diseases" form a group of fatal neurodegenerative disorders, which include, among others, scrapie in sheep, bovine spongiform encephalopathy (BSE), and Creutzfeldt-Jakob disease leads to an N-terminally truncated form of 27-30 kDa, designated PrP Sc [15]. PrP Sc is resistant towards other proteolytic enzymes like trypsin, V8 protease [11] and pepsin [8].…”
Section: Introductionmentioning
confidence: 99%
“…Transmissible spongiform encephalopathies (TSE) or "prion diseases" form a group of fatal neurodegenerative disorders, which include, among others, scrapie in sheep, bovine spongiform encephalopathy (BSE), and Creutzfeldt-Jakob disease leads to an N-terminally truncated form of 27-30 kDa, designated PrP Sc [15]. PrP Sc is resistant towards other proteolytic enzymes like trypsin, V8 protease [11] and pepsin [8].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the WB is based on a PrP-specific monoclonal antibody (6H4) c and an alkaline phosphataseconjugated antibody combined to a chemiluminescence detection system. 11 The sample is positive when the 3-band pattern of PrP27-30kD is identified. Each sample is tested in duplicate.…”
mentioning
confidence: 99%
“…However, it has largely been concluded that autolysis does not compromise the accuracy of assays that detect the proteinase-resistant, pathogenic isoform of the prion protein (PrP res ). 2,5,7,8,12,16 It was hypothesized that over a relatively long period of time, exposure to heat may have a more substantial effect on PrP res immunodection than previously considered. The objective of the present study was to characterize PrP CWD detectability with time in brain samples subjected to heat in vitro as determined by Western blot.…”
mentioning
confidence: 99%